Nasal gene expression shows a distinct signature in type 2-high asthma but not in type 2-low disease. - Karp,T; Merid,SK; Kermani,NZ; Faiz,A; Gillett,TE; Bults,R; Raby,KL; Kerstjens,HAM; Nawijn,MC; Piraino,A; Kraft,M; Beghè,B; et al. (J Allergy Clin Immunol, 2026)
BACKGROUND: Type 2 (T2)-low asthma is defined by low levels of T2 inflammation and is associated with resistance to inhaled corticosteroids. Its molecular mechanisms are mostly unknown, and treatment options are limited. We previously showed that nasal brush transcriptomes differ between asthma and controls, reflecting disease-relevant biology. OBJECTIVE: We explored nasal gene expression related to T2-low asthma in the ATLANTIS cohort. METHODS: We compared nasal brush RNA sequencing data between 82 T2-low and 63 T2-high asthma patients and 57 controls. T2-low asthma was defined as blood eosinophil counts < 0.15 × 109/L and Feno < 25 ppb and T2-high as blood eosinophil counts > 0.3 × 109/L and Feno > 25 ppb. Weighted gene coexpression network analysis (WGCNA) was applied to identify gene modules associated with T2-low asthma. The BAMSE and U-BIOPRED cohorts were used for replication analyses. RESULTS: Although differentially expressed genes were found in patients with T2-high asthma across all 3 cohorts, no differentially expressed genes were observed in individuals with T2-low disease compared to controls in ATLANTIS, nor consistently across other cohorts. Our assessment of molecular heterogeneity could not attribute this result to greater intersample variability within the T2-low group. WGCNA in ATLANTIS identified "black" and "purple" gene modules linked to T2-low asthma, with genes enriched in T-cell immunity and ribosomal RNA biology pathways, respectively. The "black" module was replicated in U-BIOPRED and showed the same direction in BAMSE. CONCLUSION: T2-high asthma shows a distinct nasal gene expression signature compared to healthy controls, while patients with T2-low asthma exhibit no consistent changes. Future studies should explore T-cell immunity in T2-low asthma and integrate lower airway multiomics data.